Optimalisasi Penyaluran dan Pengawasan Dana Lembaga Pengelola Dana Bergulir kepada Usaha Mikro Kecil dan Menengah melalui Aplikasi Securities Crowdfunding Sharia - Shela Nur Afinka; Istifaiyatul Awaliyah; Adelia Putri Ifosioni (Fakultas Syariah dan Ekonomi Islam Institut Pesantren Mathali'ul Falah, 2022)
Micro, Small and Medium Enterprises (UMKM) are one of the fields that make a significant contribution to Indonesia's economic growth, but there are still problems in limited access to productive resources, especially capital. One of the financial institutions that provide financing is the Islamic People's Financing Bank (BPRS), which in its implementation is supervised by the Financial Services Authority (OJK). The government provides funds for Revolving Fund Distribution Institutions (LPDB) to be managed by Sharia People's Financing Banks (BPRS) which will later be distributed to Micro, Small, and Medium Enterprises. This study aims to optimize the distribution and supervision of funds from the Micro, Small and Medium Enterprises Cooperative Revolving Fund Management Institution (LPDB-KUMKM) as a strengthening of Micro, Small and Medium Enterprises based on the application of sharia compliance perspective. The type of research used is the type of research and development or Research and development (R&D). The data collected in this paper are primary and secondary data as well as data analysis using qualitative descriptive methods. Co-Fund Sharia (Securities Crowdfunding Sharia) is an application-based financial technology innovation designed with sharia compliance principles, as a medium to assist the Financial Services Authority (OJK) in supervising the distribution of Revolving Fund Management Institution (LPDB) funds by Sharia People's Financing Banks (BPRS) so that the distribution of these funds can be right on target.